The Indian in Drum in the 1950s - Naidoo, Riason (My University, 2009)
ABSTRACT This investigation aims to provide evidence of alternate South African Indian identities that have been suppressed in representations of the 'Indian' in the country. In order to do this the study first establishes some of the dominant notions of the 'Indian' that include portrayals in state publications such as Meet the Indian in South Africa. The investigation then makes use of the DRUM magazine archive of articles and images relating to 'Indians' in the 1950s to deconstruct many of the popular 'Indian' stereotypes. The findings recover an unofficial 'Indian' history by recalling personalities and 'Indian' sub-cultures that emphatically demonstrate alternate 'Indian' identities. Via the findings the study thus also hopes to contribute to the restoration a communal 'Indian' memory. The inquiry also finds that this 'Indian' representation in DRUM magazine has been overlooked in the general retelling of the DRUM magazine story. The study therefore also acknowledges some of the 'Indian' writers and photographers who were responsible for documenting these stories in the magazine. This argument for a broader and more complex view of the 'Indian' is reinforced via the production of an exhibition of photographic images drawn from the DRUM magazine archive that relate directly to the discussion, which forms part of the practical visual art requirement of the degree, the production of which is discussed under a separate chapter.